2017
DOI: 10.1016/j.pec.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the interplay of cancer patients’ instrumental concerns and emotions

Abstract: The results of this study can be used to support providers in recognizing concerns that are expressed by patients in consultations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The first topic was developed to obtain an overview of the concerns patients have experienced during their illness. The findings regarding these concerns have been published elsewhere (Brandes et al, ). The second topic aimed to gather ideas for a communication tool that supports concern expression.…”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…The first topic was developed to obtain an overview of the concerns patients have experienced during their illness. The findings regarding these concerns have been published elsewhere (Brandes et al, ). The second topic aimed to gather ideas for a communication tool that supports concern expression.…”
Section: Methodsmentioning
confidence: 84%
“…Results of this previous study revealed that patients frequently explain their concerns as an interplay of instrumental concerns and emotions. We concluded that instrumental concerns must be taken into account in the operationalisation of concerns in research because instrumental concerns are often accompanied by emotions (e.g., receiving insufficient information and frustration) and emotions are often accompanied by instrumental concerns (e.g., fear and difficulties with searching, finding and judging of information; Brandes et al, ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These after-effects, some permanent, can interfere with the maintenance or recovery of roles which are important to them (Annunziata et al, 2018;Cavers et al, 2019). It is common for people to experience unpleasant thoughts and feelings regarding their experience with cancer (Brandes et al, 2017;Deimling et al, 2017). One common reaction is to attempt to avoid such feelings, encouraged and reinforced, furthermore, by the cultural context (Hayes, 2004).…”
mentioning
confidence: 99%
“…Multiple reasons can be given for these unmet needs. Patient-related reasons include unmentioned concerns, a lack of trust in a particular medical expert, and information overload [26]. Examples of medical expert-related concerns are time constraints and a lack of experience [27].…”
Section: Interpersonal Communicationmentioning
confidence: 99%